Laboratory Methods Examining the Effects of Pavement Runoff. (2017) - Rahn, Keith A.; Davis, Phillip; Dougherty, Mark
Abstract: With the growth of our nation's cities, the phenomena of the "Heat Island" effect has impacted the weather of urban areas. One of the main reasons is that our cities have a large percent of pavement that absorbs significant amounts of thermal heat during the day, which in turn is released into the environment during nighttime hours. This paper provides laboratory methods that can be used to test surface heating and cooling cycles for a variety of urban pavements including pervious and impervious concrete samples, concrete pavers, and sod. Thermal experiments using heat lamps and artificial rainfall are used to quantify the effects of insolation on the temperature of different paving materials currently used in residential and commercial development applications. Preliminary observations indicate that pervious concrete samples tend to heat up and transfer heat more rapidly than impervious concrete samples. The observation of different heat storage characteristics in pervious and impervious concrete, while not surprising, can provide insight into design applications that include direct human contact with pavement as well as environmental impacts resulting from pavement choice. Testing in a controlled laboratory environment is necessary to provide reliable thermal properties and response of paving materials as well as runoff and leachate from impervious and pervious surfaces, respectively.